Heterocycle-containing tranylcypromine derivatives endowed with high anti-LSD1 activity - Rossella Fioravanti; Veronica Rodriguez; Jonatan Caroli; Ugo Chianese; Rosaria Benedetti; Elisabetta Di Bello; Beatrice Noce; Clemens Zwergel; Davide Corinti; Dolores Viña; Lucia Altucci; Andrea Mattevi; et al. (Taylor & Francis Group, 2022)
As regioisomers/bioisosteres of 1a, a 4-phenylbenzamide tranylcypromine (TCP) derivative previously disclosed by us, we report here the synthesis and biological evaluation of some (hetero)arylbenzoylamino TCP derivatives 1b-6, in which the 4-phenyl moiety of 1a was shifted at the benzamide C3 position or replaced by 2- or 3-furyl, 2- or 3-thienyl, or 4-pyridyl group, all at the benzamide C4 or C3 position. In anti-LSD1-CoREST assay, all the meta derivatives were more effective than the para analogues, with the meta thienyl analogs 4b and 5b being the most potent (IC50 values = 0.015 and 0.005 μM) and the most selective over MAO-B (selectivity indexes: 24.4 and 164). When tested in U937 AML and prostate cancer LNCaP cells, selected compounds 1a,b, 2b, 3b, 4b, and 5a,b displayed cell growth arrest mainly in LNCaP cells. Western blot analyses showed increased levels of H3K4me2 and/or H3K9me2 confirming the involvement of LSD1 inhibition in these assays.